The story of cars - Daynes, Katie; Larkum, Adam (Usborne Pub Ltd London, Tulsa, Okla., 2005)
Covers the history of cars from early conceptions of self-propelled vehicles, through the evolution of automobile technology and design, to modern racing and speculation on the future of cars.